The Decision-Making in Planning of Housing on Musi Riverbank, Palembang - Maya Fitri Oktarini; Primadella Primadella; Listen Prima (Diponegoro University, 2023)
The riverbank has a unique landscape and socio-cultural character of the community. The area is the transition of the innerland and river ecosystem. The ecological function is very important for balancing the both ecosystems. The Living activity of dwellers creates a socio-cultural bond to the river. This study plans the housing riverbank with a socio-ecological approach. The approach considers the sustainability of the ecosystem and social culture of the dwellers. The research was conducted in Palembang, a big city in Indonesia that has evolved in wetlands on the riverbanks. The current development eliminates the character of the physical and socio-cultural landscape. This study uses the Multi-Attribute Utility Theory (MAUT) method which is part of the Multi-criteria Decision-Making (MCDM) method. MAUT can determine alternative planning through attribute assessment by predetermined objective criteria. The decision making is based on the assessment by experts from various fields. It shows the best alternative depends on the attribute level of the house type. The attribute value is very dominant compared to other attributes. Environmental attributes quite influential are the size of the buffer zone and the construction of riveredge wall. The best alternative result indicated that the planning should accommodate the activities of residents who interact closely with the sustainability of river ecosystems.